DSTYK Promotes Metastasis and Chemoresistance via EMT in Colorectal Cancer - Zhang, Jinyu; Miller, Zachary; Musich, Phillip R.; Thomas, Ashlin E.; Yao, Zhi Q.; Xie, Qian; Howe, Philip H.; Jiang, Yong (Frontiers in Pharmacology, 2020)
Objective: Tumor metastasis and resistance to chemotherapy are two critical factors that contribute to the high death rate of colorectal cancer (CRC) patients. Metastasis is initiated through the epithelial-mesenchymal transition (EMT) of tumor cells, which has emerged not only as a fundamental process during metastasis, but is also a key process leading to chemoresistance of cancer cells. However, the underlying mechanisms of EMT in CRC cell remain unknown. Here, we aim to assess the role of DSTYK in CRC metastasis and chemoresistance. Methods: To study the role of dual serine/threonine and tyrosine protein kinase (DSTYK) in TGF-β-induced EMT, we employed techniques including Crispr/Cas knockout (KO) to generate DSTYK/KO cell lines, RT-PCR to detect the mRNA expressions, immunofluorescence analysis and western blots to detect protein levels of DSTYK in following 4 cell lines: control LS411N-Tβ RII and LS411N-Tβ RII/DSTYK KO, control LS513 and LS513/DSTYK KO cells, treated with/without TGF-β1. The effects of DSTYK on apoptosis were investigated by MTT assays, flow cytometry assays, and TUNEL assays. The expression of DSTYK in colon patients and its correlation with EMT markers were determined by bioinformatics analysis. For in vivo analysis, both xenograft and orthotopic tumor mouse models were employed to investigate the function of DSTYK in chemoresistance and metastasis of tumors. Results: In this study, we demonstrated that a novel kinase DSTYK promotes both TGF-β-induced EMT and the subsequent chemoresistance in CRC cells. DSTYK KO significantly attenuates TGF-β-induced EMT and chemoresistance in CRC cells. According to the Gene Expression Omnibus (GEO) database, the expression of DSTYK is not only positively correlated to the expression of TGF-β, but proportional to the death rate of CRC patients as well. Evidently, the expression of DSTYK in the metastatic colorectal cancer samples from patients was significantly higher than that of primary colorectal cancer samples. Further, we demonstrate in mouse models that chemotherapeutic drug treatment suppressed the growth of DSTYK KO tumors more effectively than control tumors. Conclusion: Our findings identify DSTYK as a novel protein kinase in regulating TGF-β-mediated EMT and chemoresistance in CRC cells, which defines DSTYK as a potential therapeutic target for CRC therapy.